Java projects : learn the fundamentals of Java 11 programming by building industry grade practical projects - Verhas, Peter (Packt Publishing, 2018)
Java is one of the most commonly used software languages by programmers and developers. In this book, you'll learn the new features of Java 11 quickly and experience a simple and powerful approach to software development. You'll see how to use the Java runtime tools, understand the Java environment, and create a simple namesorting Java application. Further on, you'll learn about advanced technologies that Java delivers, such as web programming and parallel computing, and will develop a mastermind game. Moving on, we provide more simple examples, to build a foundation before diving into some complex data structure problems that will solidify your Java 11 skills. With a special focus on the features of new projects: Project Valhalla, Project Panama, Project Amber, and Project Loom, this book will help you get employed as a top-notch Java developer. By the end of the book, you'll have a firm foundation to continue your journey toward becoming a professional Java developer.